If the parabola has y = -4 at both x = 2 and x = 3, then since a parabola is symmetric, its axis of symmetry must be between x = 2 and x = 3, or at x = 5/2. Our general equation can then be:
y = a(x - 5/2)^2 + k
Substitute (1, -2): -2 = a(-3/2)^2 + k
-2 = 9a/4 + k
Substitute (2, -4): -4 = a(-1/2)^2 + k
-4 = a/4 + k
Subtracting: 2 = 2a, so a = 1. Substituting back gives k = -17/4.
So the equation is y = (x - 5/2)^2 - 17/4
Expanding: y = x^2 - 5x + 25/4 - 17/4
y = x^2 - 5x + 2 (This is the standard form.)
Answer:
vyuWYIRTG3ñwyiehg
Step-by-step explanation:
Answer:
Step-by-step explanation:
3. Use Cosine law to find the length of the unknown side (PR)
q² = p² + r² - 2prCos Q
q is the opposite side of ∠Q;
p is the opposite side of ∠P; p = 33
r is the opposite sides of ∠R ; r = 67
q² = 33² + 67² - 2* 33*67 Cos 19°
= 1089 + 4489 - 4422 * 0.95
= 1089 + 4489 - 4200.9
= 1377.1
q = √1377.1
q = 37.1
PR = 37.1
To find the angle use law of sin

Sin P = 0.3

P = 17.5°
∠R = 180 - (19 + 17.5)
= 143.5°
Answer:
24 units ^2
Step-by-step explanation:
The base runs from 3 to 7 so the base is 7-3 = 4 units
The height runs from 2 to 8 so the height is 8-2 = 6 units
The area is
A = bh
= 6*4 = 24 units ^2
Answer:
A. 0
E. -3
F. 9
Step-by-step explanation:
You can't divide by 0; it is undefined. So if x cannot equal zero, then anything that turns the denominator to zero is an asymptote. Therefore, the roots of the cubic expression would be excluded, and we get our final answers.